PRICE EARNING RATIO, AVERAGE VOLUME AND STOCK BETA OF INDONESIA SE HEALTHCARE COMPANIES - Francis Hutabarat (Program Studi Magister Manajemen Universitas Advent Indonesia, 2022)
This research is entitled Price Earning Ratio, Average Volume and Stock Beta of Indonesia SE Healthcare Companies. This research method uses multiple linear regression analysis with data processing using the PSPP software. The sampling method of this research uses purposive sampling technique. The results showed that simultaneous Price earning ratio and average volume had significant affect on stock beta. The results of the t test show that the variables Price earning ratio and average volume partially have significant effect on stock beta with a significance level of 2,4%, and 4,2%, respectively.